Dealing with Idioms: An Eye-Tracking Study of Cognitive Processing on L1, L2 and Heritage Speakers of Spanish - Pilar Valero Fernández; Adriana Cruz; Mathis Teucher; Inés Recio Fernández; Óscar Loureda Lamas (Languages)
This study investigates the cognitive processing of Spanish idioms from a pragmatic perspective, with the goal of examining the idiom superiority effect. An eye-tracking experiment was conducted with 77 participants to assess how idiomaticity influences processing and whether heritage speakers align more with L1 or L2 patterns. Results show a processing advantage for idioms among L1 speakers, suggesting reduced cognitive load in later stages. Both heritage and L2 speakers showed longer reading times, but only L2 speakers benefited consistently from idiomaticity. Heritage speakers processed idioms more slowly, indicating difficulty with opacity despite early exposure. Findings support hybrid models of idiom processing and highlight the unique strategies of heritage speakers shaped by dual input sources.